A-Z of nutritional supplements: dietary supplements, sports nutrition foods and ergogenic aids for health and performance: Part 47 - Burd, N. A.; Stear, S. J.; Burke, L. M.; Castell, L. M. (British Journal of Sports Medicine, 2013)
Not surprisingly, we originally intended that the last word on our A-Z supplement series should come under `Z`. However, we did not anticipate the attention provided to a topic that we had over-looked under `P`, namely peptides. Some peptides - technically defined as chains of amino acids of lengths ranging from 2 to 50—can be considered nutrients. Indeed, there is now increased recognition that some proteins in our diet (eg, milk proteins) are broken down and absorbed in such fragments, exerting biological effects of their own in addition to their contribution to the body`s amino acid pool. However, it is synthetic peptides that have become a major talking point in sport,due to publicity in 2013 regarding their alleged use in some professional football codes in Australia as part of a `supplement scheme`. These products include chemicals that have been registered in clinical trials as potential secretagogues of growth hormone. Whether some of these products are unapproved medicines or supplements found on websites targeting body builders has become blurred. Because of the apparent confusion and controversy over such products, we have invited a special editorial on the topic.